GPR35 as a Novel Therapeutic Target - MacKenzie, Amanda; Lappin, Jennifer; Taylor, Debra; Nicklin, Stuart; Milligan, Graeme (Frontiers in Endocrinology, 2011)
G protein-coupled receptors (GPCRs) remain the best studied class of cell surface receptors and the most tractable family of proteins for novel small molecule drug discovery. Despite this, a considerable number of GPCRs remain poorly characterised and in a significant number of cases, endogenous ligand(s) that activate them remain undefined or of questionable physiological relevance. GPR35 was initially discovered over a decade ago but has remained an ‘orphan’ receptor. Recent publications have highlighted novel ligands, both endogenously produced and synthetic, which demonstrate significant potency at this receptor. Furthermore, evidence is accumulating which highlights potential roles for GPR35 in disease and therefore, efforts to characterise GPR35 more fully and develop it as a novel therapeutic target in conditions that range from diabetes, hypertension to asthma are increasing. Recently identified ligands have shown marked species selective properties, indicating major challenges for future drug development. As we begin to understand these issues, the continuing efforts to identify novel agonist and antagonist ligands for GPR35 will help to decipher its true physiological relevance; translating multiple assay systems in vitro, to animal disease systems in vivo and finally to man.